Adrenal incidentalomas, cortisol secretion and cancer: is there a real crosstalk? - Herrera-Martínez, Aura D.; Román, Ángel Rebollo; Corrales, Eider Pascual; Idrobo, Cindy; Ramírez, Paola Parra; Rojas, Patricia Martín; Lázaro, Cristina Robles; Araujo-Castro, Marta (Frontiers in Endocrinology, 2024)
Background Cortisol has immunomodulatory effects that increase the risk and evolution of several diseases. Cancer is characterized by a proinflammatory state in which cells exert impaired function and proliferation. The relation between cortisol secretion and increased risk of malignant neoplasm, or their behavior, has not been fully elucidated. Aim To determine the relation between cortisol secretion and the prevalence and clinical outcome of malignant neoplasms in patients with adrenal incidentalomas (AIs). Methods Multicenter retrospective study that included 935 patients with AIs. Cortisol secretion was defined by a cortisol post-dexamethasone suppression test > 1.8 µg/dL, and nonfunctioning AIs (NFAIs) as a value ≤ 1.8 µg/dL. Results Cortisol secretion was evident in 30.8% of the patients and cancer in 23.6% (especially breast, colorectal, prostate and thyroid cancer). No differences in the cancer prevalence were found between patients with cortisol secretion and NFAIs (63.6% vs. 63.4%, p=0.10). After adjusting by age, cortisol secretion was not associated with the presence of cancer (OR 1.29, CI 0.93–1.78). However, cortisol secretion was significantly associated with stage IV of cancer at diagnosis (OR 2.68, CI 1.19– 6.00) and mortality (OR 3.2, CI 1.28- 7.97). Patients with NFAI and breast cancer required treatment with chemo- and radio-therapy more frequently that patients with cortisol secreting AI (90% vs 10% and 92.9% vs 7.1% respectively, p<0.05), similarly patients with prostate cancer required radiotherapy more frequently (90.9% vs 9.1%, p=0.05); also, patients with colorectal cancer and NFAI, tended to require chemotherapy more frequently(76.5% vs 23.5%, p=0.06). Conclusion Cortisol secretion does not increase the risk of malignant neoplasm, but it affects its clinical course, treatment requirements and mortality, leading to a worst prognosis and higher mortality when compared with patients with NFAIs.